2021
DOI: 10.21037/atm-20-6704
|View full text |Cite
|
Sign up to set email alerts
|

Hypertermic Intrathoracic Chemotherapy (HITHOC) for thymoma: a narrative review on indications and results

Abstract: Objective: With this narrative review, we retraced the history of hypertermic intrathoracic chemotherapy (HITHOC) since the beginning, analyzing literature on operative technique, feasibility and efficacy of this treatment. Moreover, we report the fifteen-year experience of our center in this relatively new technique, for what concerns both early postoperative results and long-term oncological outcomes.Background: Thymomas are frequently misdiagnosed and recognized in advanced stage, often with pleural dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Secondly, we were able to demonstrate using the French database RYTHMIC that surgical excision of pleural nodules (including HITHOC cases) in stage IVa compared to systemic treatments reduced the risk of recurrence by 60% (HR = 0.4, 95 CI (0.25–062); p < 0.0001) [ 25 ]. These results were confirmed by the study of Aprile et al [ 26 ], who were able to demonstrate in a retrospective study that the HITHOC procedure coupled with a cytoreductive pleurectomy gave better results in DFI compared with cytoreduction alone: 88 ± 15 vs. 57 ± 19 months ( p = 0.046). Moreover, our results are fully comparable with those previously published showing a 5-year survival rate between 70–100% and a DFI of 61–87% [ 27 ].…”
Section: Discussionsupporting
confidence: 65%
“…Secondly, we were able to demonstrate using the French database RYTHMIC that surgical excision of pleural nodules (including HITHOC cases) in stage IVa compared to systemic treatments reduced the risk of recurrence by 60% (HR = 0.4, 95 CI (0.25–062); p < 0.0001) [ 25 ]. These results were confirmed by the study of Aprile et al [ 26 ], who were able to demonstrate in a retrospective study that the HITHOC procedure coupled with a cytoreductive pleurectomy gave better results in DFI compared with cytoreduction alone: 88 ± 15 vs. 57 ± 19 months ( p = 0.046). Moreover, our results are fully comparable with those previously published showing a 5-year survival rate between 70–100% and a DFI of 61–87% [ 27 ].…”
Section: Discussionsupporting
confidence: 65%
“…To reinforce the data obtained by Ried et al [ 2 ], Chappuy et al [ 10 ] reported an important experience with 40 patients with T IVa pleural involvement treated with partial pleurectomy and HITHOC showing a median length of survival of 118 months and a median DFI of 70 months [ 10 ]. The group of Pisa in Italy had also similar results [ 11 ].…”
mentioning
confidence: 55%
“…Aggressive trimodality treatment approach has been evaluated in patients with secondary pleural metastasis 15,16 . This combination has been effective in achieving local control and improved 5‐ and 10‐year survivals in selected patients with metastatic thymic malignancies 28–30 . All of our thymoma patients are alive after their P/D and HITEC at a median follow‐up of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 This combination has been effective in achieving local control and improved 5-and 10-year survivals in selected patients with metastatic thymic malignancies. [28][29][30] All of our thymoma patients are alive after their P/D and HITEC at a median follow-up of 24 months. Thymic metastases are usually more indolent than malignant mesothelioma or other secondary pleural metastasis.…”
Section: Thymic Cancermentioning
confidence: 98%